COVID-19-associated shortage of alcohol-based hand rubs, face masks, medical gloves, and gowns: proposal for a risk-adapted approach to ensure patient and healthcare worker safety. Issue 3 (July 2020) - Kampf, G.; Scheithauer, S.; Lemmen, S.; Saliou, P.; Suchomel, M.
Summary: The coronavirus disease 2019 (COVID-19) pandemic has caused a huge demand for alcohol-based hand rubs, medical gloves, face masks, and gowns in healthcare and from the public. More and more hospitals face a serious shortage of these articles. We propose a risk-adapted approach to ensure adequate patient and healthcare worker safety for as long as possible.